2012
DOI: 10.2134/agronj2011.0399
|View full text |Cite
|
Sign up to set email alerts
|

Crop Productivity and Nutrient Dynamics in a Shrub (Guiera senegalensis)–Based Farming System of the Sahel

Abstract: Piliostigma reticulatum (DC.) Hochst., an indigenous shrub, forms an important vegetative component of parkland cropping systems in the Sahel; however, its biophysical interactions with soil and crops are not well understood. Therefore, the objectives were to determine the impact of P. reticulatum, under varying fertilizer rates, on crop yield response and soil nutrient dynamics. The experiment had a split‐plot factorial design, where the main plot was shrub (presence or absence) and the subplot was fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 45 publications
6
41
5
Order By: Relevance
“…Millet growth promotion was observed at both study sites in plots intercropped with woody shrubs. For the Keur Matar site, the results of this study are consistent with previous findings (9) in which millet (and groundnut) grown in the presence of G. senegalensis had substantially greater yields over 4 cropping seasons than sole crops. In that study, the application of an intercropping system with the addition of shrub residue took 4 cropping seasons to build the soil organic carbon and alter soil nutrient status.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Millet growth promotion was observed at both study sites in plots intercropped with woody shrubs. For the Keur Matar site, the results of this study are consistent with previous findings (9) in which millet (and groundnut) grown in the presence of G. senegalensis had substantially greater yields over 4 cropping seasons than sole crops. In that study, the application of an intercropping system with the addition of shrub residue took 4 cropping seasons to build the soil organic carbon and alter soil nutrient status.…”
Section: Discussionsupporting
confidence: 91%
“…This study has shown that intercropping and shrub residue application can have a substantial effect on microbial communities, with individual OTUs expressing high levels of enrichment in intercropping systems (9,10). Moving forward from these associations between individual OTUs and plant health status to the identification of microorganisms which might provide beneficial functions for improved crop growth will require the isolation and functional characterization of strains corresponding to the OTUs identified here.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Agroforestry, where woody species are allowed to grow in cropped fields, is an approach that improves soils (Lorenz and Lal, 2014;Dossa et al, 2010Dossa et al, , 2009Dossa et al, , 2008, protects against water and wind erosion (Sileshi et al, 2011), and can increase crop yields (Dossa et al, , 2012Sileshi et al, 2012); benefits that collectively increase resilience to climate change, particularly in sub-Saharan Africa (Lasco et al, 2014). Here, farmers have long practiced what is called the parkland system where trees are randomly distributed in fields.…”
Section: Introductionmentioning
confidence: 99%
“…Hochst. (Fabaceae) -have been shown to have higher soil quality (Dossa et al, 2012 conferring improved crop yields (Dossa et al, 2012 compared to soils where shrubs are absent. Additionally, Kizito et al (2012) showed that G. senegalensis and P. reticulatum perform hydraulic lift; the passive movement of water from relatively moist areas to drier areas in the soil (Caldwell et al, 1998).…”
Section: Introductionmentioning
confidence: 99%